2022
DOI: 10.1186/s41043-022-00323-9
|View full text |Cite
|
Sign up to set email alerts
|

A combination of moderate and vigorous physical activities reduces the burden of multimorbidity: findings from Longitudinal Ageing Study in India

Abstract: Background Physical inactivity is a significant factor contributing to the prevalence of non-communicable diseases (NCDs). The objective of this study is to examine the association between physical activity and multimorbidity among Indian adults aged 45 years and above by residence. Methods Data from Longitudinal Ageing Study in India (LASI) 2017–2018, wave 1, a nationally representative study, are used to examine the above objective. A total of 59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…Among the participants of this study, MM was associated with longer sitting [38]. A long-term study conducted in India demonstrated that the volume of PA was inversely proportional to the prevalence of MM [39]. The same study also showed that the prevalence of MM was lower in individuals who engaged in both moderate and vigorous PA than in those who engaged only in moderate PA.…”
Section: Discussionsupporting
confidence: 54%
“…Among the participants of this study, MM was associated with longer sitting [38]. A long-term study conducted in India demonstrated that the volume of PA was inversely proportional to the prevalence of MM [39]. The same study also showed that the prevalence of MM was lower in individuals who engaged in both moderate and vigorous PA than in those who engaged only in moderate PA.…”
Section: Discussionsupporting
confidence: 54%